Examining the burial contexts and trauma patterns of fallen soldiers and civilian victims from the Spanish Civil War: a comparative investigation - Ronner, Eva; Márquez-Grant, Nicholas; Lescure, Javier; Benito Sánchez, María (Taylor & Francis, 2025)
This paper compares the context of the burials of combatants with the burial circumstances of civilian victims from the Spanish Civil War and dictatorship, along with the biological profile and trauma patterns of the remains and associated artefacts. The burial context of the 41 individuals from two cemetery mass grave sites was compared to remains from the International Brigades that were found outside in Central Spain. Different patterns were apparent regarding material culture associations, such as in the presence of ammunition with the brigadiers who had been left where they died in combat, whilst the civilians had few personal effects. Trauma patterns were also compared among the different sites, and the trauma sustained by the Brigadiers differed from that of the civilians who had been killed. Awareness of differing patterns common to combatants and civilians during the Spanish Civil War can assist in efforts to identify remains from this conflict.
Keywords: 4301 Archaeology; 4303 Historical studies; Spanish Civil War; burial context; mass graves; medicolegal investigation; forensic anthropology; international brigades; trauma analysis